Pendekatan Filologi Edwar Djamaris dalam Makna Mantra Tradisi Cowongan di Desa Pangebatan - Lutfiana, Annisa; Mawardi, Kholid (Lembaga Yasin AlSys, 2025)
This research aims to examine the meaning of mantras in the cowongan tradition in Pangebatan Village, Karanglewas District, Banyumas Regency, using Edward Djamari's philological approach. Cowongan, which was originally a tradition for farmers to request rain during the long dry season, is now revived as a performance art and is no longer a ritual for requesting rain. This research uses a field research approach with data collection techniques through observation and interviews with stakeholders and the local community. The meaning of the mantra in the cowongan performance is analyzed using philological theory. The research results show that through the mantra, the shaman feels gratitude and admiration for the wisdom of the ancestors who were able to read natural events and compose words into meaningful prayers. One of the mantra lyrics describes the kolang-kaling fruit, which holds a lot of water and grows in sloped areas, symbolizing a spring as a source of inherited happiness. Cowongan, which now serves as an art performance, continues to preserve and honor the ancestral culture passed down to future generations.